Efectos en el crecimiento inicial de Gmelina arborea Roxb. probando tres tipos de sustrato en los viveros de la finca experimental “La Represa”, año 2021. - Velalcázar Rengifo, Ana Liseth (2021)
The objective of the present study was to evaluate the effects of 3 types of substrates on the initial growth of Gmelina arborea (melina) in the experimental farm "La Represa", belonging to the State Technical University of Quevedo. The substrates that were used were: black earth as a control, rice husk, sand and PRODEUTEQ fertilizer, each one of them except the control was mixed with black earth in a percentage of 75% black earth and 25% the substrate. Prior to sowing the seeds, the drawers were cleaned and disinfected. The seedlings began to germinate in the second week after sowing and continued to germinate gradually. In the eighth week, the seedlings were removed from the tubes and taken to the laboratory of the experimental farm "La María" in order to obtain the data of dry and wet weight by using the stoves for 48 hours. It was possible to determine that the substrate in which there were the greatest number of plants was in the substrate Black earth and sand. Keywords: Substrate, germination, sowing, seedlings